Merger Policy to Promote Global Players? A Simple Model - Andreas Haufler; Søren Bo Nielsen (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
We use a simple framework where firms in two countries serve their respective domestic markets and a world market to analyze under which conditions cost-reducing mergers will be beneficial for the merging firms, the home country, and the world as a whole. For a national merger, the policies enacted by a national merger authority tend to be overly restrictive from a global efficiency perspective. In contrast, all international mergers that benefit the merging firms will be cleared by either a national or a regional regulator, and this laissez-faire approach is also globally efficient. Finally, we derive the properties of the endogenous merger equilibrium.
urn:nbn:de:bvb:19-epub-666-9
Keywords: L41; F13; H77; 330; merger policy; international trade